Pengaruh Efisiensi Biaya Bahan Baku, Biaya Tenaga Kerja Langsung, Dan Biaya Overhead Pabrik Terhadap Rasio Profit Margin - Kiki Alfiah; Suparno Suparno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of raw material cost efficiency, direct labor efficiency, factory overhead cost efficiency on the profit margin ratio in Food and Beverage Companies Listed on the Indonesia Stock Exchange. The method used is quantitative analysis, namely through classical assumption test to analyze the data and determine the level of closeness of the relationship and the effect given Efficiency of raw material costs, direct labor costs, factory overhead cost efficiency to profit ratio analysis using SPSS software. While the data used is secondary data with the type of time series data (time series) in 2013-2017. Based on the research, it is known that material cost efficiency has no significant effect on the profit margin ratio because t_count < t_table with a significantly smaller value of 0.05. Direct labor costs have a significant effect on the profit margin ratio because t_count > t_table with a significant value greater than 0.05 partially has an effect of Direct Labor Cost Efficiency on Profit Margin Ratio. The efficiency of factory overhead costs shows that t_count < t_(table.) That is a significant value of 0.725 > 0.05. Raw Material Cost Efficiency, Direct Labor Cost Efficiency, Factory Overhed Cost Efficiency in food and beverage companies in 2013 – 2017 simultaneously did not affect the profit margin ratio. Keywords: Raw Material Cost Efficiency, Direct Labor Cost Efficiency, Overhead Cost Efficiency, Profit Margin Ratio